The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/13561820.2021.1903405
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of experienced health professionals in an interprofessional context: results from a cross-sectional survey in Germany

Abstract: Interprofessional teamwork often suffers from the existence of negative stereotypes. To combat their prevalence, interprofessional education (IPE) activities are being implemented worldwide. The aim of this study is to inform IPE developers of the prevalence and content of interprofessional stereotypes in the workplace in Germany and similarly structured healthcare systems. We surveyed health professionals with several years of work experience as nurse, midwife, or therapist concerning their attitudes toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The idea of being subordinated to the medical profession also influences the self-concept and professional identity of nurses [4] and their social perception. It is sometimes argued that the social prestige of nursing is poor because it is compared to other professions such as medicine [35,44], highlighting that choosing to study medicine as opposed to nursing is linked to the higher status of medicine [14]. Nevertheless, nurses' knowledge, skills, and abilities, which underpin the profile defined in the aforementioned programmes, do equip them with the competences to work autonomously and independently.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of being subordinated to the medical profession also influences the self-concept and professional identity of nurses [4] and their social perception. It is sometimes argued that the social prestige of nursing is poor because it is compared to other professions such as medicine [35,44], highlighting that choosing to study medicine as opposed to nursing is linked to the higher status of medicine [14]. Nevertheless, nurses' knowledge, skills, and abilities, which underpin the profile defined in the aforementioned programmes, do equip them with the competences to work autonomously and independently.…”
Section: Discussionmentioning
confidence: 99%
“…The woman-nurse nexus is more pronounced in other studies, where nursing is viewed as a job aimed at women [41]; characteristic of women [40,43,46]; suitable only for women [39], and more appropriate for women [32]. This stereotype is identified by professionals themselves: 56% of men and 50.75% of women in Stanley and colleagues' article [49]; male nurses [27]; and female nurses who feel that nursing is an appropriate, suitable profession for them [40].…”
Section: Theme 1 Stereotypes Relating To Professionals' Gendermentioning
confidence: 99%
“…This factor was expressed by young people seeking to study medicine, who believed that they would obtain greater power and status as doctors than as nurses [30,48]. In Kämmer and colleagues' study [43], a participant commented that nurses belong to a different social class and are poorer than doctors. However, the participants in another research study rated nursing as the second most valued profession after medicine [46].…”
Section: C10 a Valued But Not Prestigious Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, despite the empirical evidence of divergent teamwork perceptions, only a few studies have examined the underlying reasons for the observed differences. Possible reasons that have been discussed include that expectations ( Frasier et al, 2017 ), communication styles ( Jones and Durbridge, 2016 ), and stereotypes ( Lingard et al, 2005 ; Kämmer and Ewers, 2021 ) vary with roles and profession—and hence shape perceptions. In addition, even though teams have a shared team goal, subtasks likely vary by role and profession and may thus influence the perceived strain ( Keller et al, 2021 ) and perspective on the overall teamwork quality.…”
Section: Introductionmentioning
confidence: 99%